State of levator muscles as one of the factors in development of pelvie pain syndrome among men - A. I. Neimark; M. P. Zakharova (Бюллетень сибирской медицины, 2012)
The article presents the experience of transrectal ultrasound research of muscles — levators (muscles that lift the anus) and prostate gland among 33 patients with chronic pelvic pain syndrome using the method of duplex scanning. Changes in the speed characteristics of the vessels in the levators and prostate gland allow to specify the positive dynamics of therapeutic measures (in our case and after laser treatment) and so improve the quality of patients´ life.